Utilizing the Alterable Solubility of Chitosan in Aqueous Solution to Synthesize Nanosized Sulfur for High Performance Li–S Batteries. Issue 8 (13th June 2019) - Zhang, Yu; Li, Wen‐Cui; He, Bin; Yu, Xiao‐Fei; Hou, Lu; Lu, An‐Hui
Summary of main observation and conclusion: We demonstrate the synthesis of cathode material with nanosized sulfur by a precipitation method making use of the alterable solubility of chitosan (CTS) in aqueous solution. Mesoporous Ketjen Black (KB) and carbon nanotube (CNT) are added as conductive agents to provide the three‐dimensional electric channels. This method can reduce the size of the sulfur particles, thus the nanosized sulfur obtained can fully contact with the conductive agent, which could increase the utilization of sulfur and improve the capacity of Li‐S batteries. Moreover, CTS with abundant hydroxyl and amine groups has strong interaction with polysulfides, which can improve the stability of Li‐S batteries. As a result, the obtained CTS/C‐S cathode containing 76 wt% sulfur delivers an impressively initial discharge specific capacity of 1141.6 mA·h·g –1 at 0.5 C and maintains a capacity of 842.3 mA·h·g –1 after 300 cycles. Our finding paves a way for the rational design of high‐performance sulfur cathodes for advanced Li‐S batteries. Abstract :